Investigations on the Physico-Chemical Parameters and Bacterial Occurrence in Four Water Bodies of Bhopal, India (Global Journal of Science Frontier Research, 2013)
This study was carried out in four water bodies of Bhopal for a period of 2 years. Monthly changes in physicchemical parameters such as air temperature, water temperature, total dissolved solids, hydrogen-ion concentration, dissolved oxygen, free carbon dioxide, phenolphthalein alkalinity, total alkalinity, chloride, calcium hardness and total hardness along with bacterial occurrence were studied. The results indicated changes in physicchemical parameters and occurrence of bacteria depending on the different seasons of the year.
Keywords: physic-chemical parameters; water bodies; monthly changes